Digest: Colonizing rodents overcome ecological incumbency in an island system*. (29th May 2019) - Roycroft, Emily J.
Abstract: Do primary radiations inhibit the persistence and diversification of secondary colonizers? Rowsey et al. test predictions of this "incumbency effect" by contrasting patterns of morphological variation in two murine rodent clades on the Philippine island of Luzon. They find that in this system, primary colonizers may impose constraints via biotic filtering, and may also restrict size evolution in secondary colonists.